Terapi Aktivitas Senam Ergonomis terhadap Peningkatan Kemampuan Fungsional Lansia - Juli Andri; Resi Karmila; Padila Padila; Harsismanto J; Andry Sartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to analyze the effect of ergonomic exercise on the Improvement of Functional Ability in the elderly in the Posyandu Elderly Work Area of the Sukamerindu Public Health Center in Bengkulu City, which decreased Functional Ability. The design of this study used a quasi-experimental design with pre-test and post-test without comparison (control) groups. Paired T-test results showed an increase in the value of functional ability with P Value = 0,000 <0.05. Conclusion, there is an influence of ergonomic exercise activity therapy on increasing functional ability in the elderly. Keywords: Functional Ability, Elderly, Ergonomic Gymnastics